Characterisation of antibody raised against the E7 protein of Human papillomavirus type 11 and its application in clinical samples. - Lim, Yin Jia. (2010)
Human Papillomavirus (HPV) E7 protein, like E6, is an oncoprotein in high-risk HPV types known to be highly expressed in cervical carcinomas. This is however not established for low-risk HPV infections by HPV6 and 11 that induce cell proliferation giving rise to benign condylomata. In this project, polyclonal antibodies were raised against the E7 protein of HPV11 (11E7). Its specificity was tested using Western Blot, Immunofluorescence and Immunohistochemistry. We verified that it could recognise 11E7 and presumably 6E7 due to high sequence homology, but does not cross-react with E7 of high-risk types. The purified antibody was used to detect E7 protein directly in formalin-fixed, paraffin-embedded clinical condyloma samples where its expression was found to be very low, suggesting that low-risk E7 may not represent a sensitive marker for the disease. Interestingly, there is pronounced labeling of E7 in the basal layer of the squamous epithelium adjacent to the condylomata, implying that E7 is expressed in greater amounts in the initial stage of infection (when the cervical histological structure has yet to be disrupted) but down-regulated thereafter. The precise mechanism of condyloma formation remains unknown but we speculate that high levels of E7 may not be required for the maintenance of these benign warts.